The effect of chatter on cutting tool in CNC milling machine - Crispin, Julip Jainul (2009)
This study focuses on chatter analysis after undergone milling process. The first objective of this project is to get the value of chatter using DYNO-METER on the CNC milling machine. After getting value of chatter, the second objective is to analyze the chatter using ALGOR software. The output that needs to get is in term of stresses. Minitab software also was performed to analyze the parameters involved in the experiment. In this project, Master Cam software will be used to design the work piece that will be used throughout this study. This software also will be used to simulate and generate the G-code to help user to operate with CNC milling machine. The work piece material that will be used was high carbon steel (AISI-D12) and its parameter is 100x100x50 mm. From the results obtained after machining, the most significant factor for the chatter were depth of cut and spindle speed. This means whenever the depth of cut is too depth and the spindle speed is slow, the maximum chatter will occurred with high cutting force applied. From the Algor analysis, the results showed that the different forces will result in different value of stresses. It is obvious that when cutting force is higher, the value of stress is also higher. The depth of cut also influences the chatter in this study. Spindle speed and feed rate should have an appropriate setting in to reduce the chatter. Based on this study, the analysis showed that higher chatter tends to increase the tool wear or tool breakage.